2019
DOI: 10.33545/gynae.2019.v3.i1c.25
|View full text |Cite
|
Sign up to set email alerts
|

Association of postnatal umbilical coiling index with maternal & perinatal outcome

Abstract: To measure umbilical coiling index (UCI) postnatally and to study the association of normocoiling, hypo coiling and hyper coiling to maternal and perinatal outcome. Method: Two hundred antenatal women who went into labour were studied and umbilical coiling index calculated at the time of delivery. UCI was determined by dividing the total number of coils by the totalumbilicalcordlengthincentimetres.Itsassociationwithselected maternal risk factors and fetal outcome were noted. The statistical tests were the Chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
2
3
2
Order By: Relevance
“…11 This was in correlation with Mittal et al and Pergialiotis et al 12,13 However, in the present study, there was no such significance. Khan et al concluded that there was no significant association between mode of delivery and umbilical cord coiling index which was in correlation with the study done by Dijk et al 14,15 The present study also concluded the same. A study conducted by Razak K et al stated that hypocoiled cords were associated with more number of low birth weight babies.…”
Section: Resultssupporting
confidence: 91%
“…11 This was in correlation with Mittal et al and Pergialiotis et al 12,13 However, in the present study, there was no such significance. Khan et al concluded that there was no significant association between mode of delivery and umbilical cord coiling index which was in correlation with the study done by Dijk et al 14,15 The present study also concluded the same. A study conducted by Razak K et al stated that hypocoiled cords were associated with more number of low birth weight babies.…”
Section: Resultssupporting
confidence: 91%
“…In this study, statistically significant association was seen between hypercoiling and anemia (p = 0.005) whereas no association was found in study conducted by Chitra et al 1 The mean birth weight in this study was 2671 ± 5.9 gm with hypercoiling being significantly associated with LBW (p = 0.016). Consistent findings were reported by Mittal et al, 7 Khan and Thakur, 14 and Agarwal et al 15 It has been observed that if coiling is increased beyond a certain limit, the uteroplacental flow decreases, leading to LBW.…”
Section: Number Of Vascular Coils In the Cordsupporting
confidence: 82%
“…Similar findings were noted by study conducted by Khan and Thakur. 14 In this study, no significant association was found between UCI and preterm labor, whereas in a study by Strong et al 3 and de Laat et al 9 association was seen between hypocoiling and preterm labor although no satisfactory explanation was found.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The umbilical cord (UC), along with the placenta, is the only organ that dies when life begins. Although the umbilical cord is one of the most interesting organs in humans, it remains one of the least studied structures (Khan and Thakur, 2019).…”
Section: Introductionmentioning
confidence: 99%